2015
DOI: 10.1017/s2078633615000235
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree analysis of the Afrikaner cattle breed

Abstract: SummaryThe reduction of genetic variability in beef cattle has been extensively researched on a global scale. However, the genetic variability and inbreeding of indigenous cattle breeds of Southern Africa, referred to as Sanga cattle, has been less well characterized. Breeds of Sanga cattle include Afrikaner, Drakensberger and Nguni breeds. In recent years, the number of Afrikaner cattle and herds has decreased. Our objective was to determine the mean level of inbreeding (F), effective population size (Ne) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Similar values have been reported for the Afrikaner breed by Beffa et al (2009) (4.4 for males and 6.5 females) and Pienaar et al (2015) with an average of 6.6 years. These estimates of generation intervals are slightly longer compared with the reported generation interval of 5.6 and 5.2 years for the Bonsmara, a local composite breed in South Africa (Groeneveld et al, 2009).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Similar values have been reported for the Afrikaner breed by Beffa et al (2009) (4.4 for males and 6.5 females) and Pienaar et al (2015) with an average of 6.6 years. These estimates of generation intervals are slightly longer compared with the reported generation interval of 5.6 and 5.2 years for the Bonsmara, a local composite breed in South Africa (Groeneveld et al, 2009).…”
supporting
confidence: 87%
“…The rates of inbreeding (∆F) per generation for all five breeds (Table 3) are less than 1% and the effective population sizes are all well above the minimum level for concerns of loss of diversity. In a recent study, an effective population size as high as 167 have been reported for the Afrikaner breed (Pienaar et al, 2015). The rate of inbreeding and effective population size for the Boran breed cannot be regarded as a true reflection for these parameters due to incomplete pedigree recording.…”
mentioning
confidence: 98%
“…Pedigree analysis is an appropriate tool for the evaluation of genetic diversity of a population. This method has been commonly used for the study of the genetic variability in pig (Szab o et al 2016), sheep (Mokhtari et al 2014), cattle (Pienaar et al 2015), buffalo (Marcondes et al 2014), horse (Hasler et al 2011), donkey (Cecchi et al 2006) and in pet animals (Cecchi et al 2013). A limited number of studies have also evaluated genetic diversity of goat breeds through this method (Portolano et al 2004;Baldursdottir et al 2012;Oravcov a 2013;Rashidi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tuli had the highest number (17) of PAs, showing that the breed has been developed as a distinctive genotype without significant admixture from the other two breeds. Breed PAs have been observed in diversity studies on indigenous cattle in Ethiopia (Edea et al, 2013;Ngono-Ema et al, 2014), South Africa (Pienaar et al, 2015;Sanarana et al, 2016), and Mozambique (Bessa et al, 2009). The Na and Ne alleles revealed no appreciable differences in the level of genetic variability among these breeds.…”
Section: Discussionmentioning
confidence: 96%
“…Sanga-type cattle constitute the bulk of the cattle genetic resources in this region and include breeds such as the Nguni, Drakensburger and Afrikaner of South Africa, Landim of Mozambique, Sanga of Namibia, Nguni of Swaziland and Zambia, and Mashona, Nkone and Tuli of Zimbabwe (Ramsay, 2010;Pienaar et al, 2015;Nyamushamba et al, 2017). It is presumed that the Sanga group of cattle resulted from the crossbreeding of African taurine and zebu cattle around 700 AD in Ethiopia, followed by migration to southern Africa with tribesmen via the tsetse-free Mozambique corridor (Felius et al, 2014).…”
Section: Introductionmentioning
confidence: 99%